C-phycocyanin alleviated cisplatin-induced oxidative stress and inflammation via gut microbiota—metabolites axis in mice - Zhang, Yubing; Li, Lili; Qin, Song; Yuan, Jingyi; Xie, Xiaonan; Wang, Fan; Hu, Shanliang; Yi, Yuetao; Chen, Min (Frontiers in Nutrition, 2022)
C-phycocyanin is a natural protein extracted from Spirulina platensis. We aim to investigate the preventive effect of C-phycocyanin on cisplatin chemotherapy-induced oxidative damage and inflammation. The result showed that C-phycocyanin treatment reduced cisplatin-induced mortality and inflammation including decreased levels of serum IL6, kidney MCP1, and liver IL1β. Furthermore, C-phycocyanin also exerted antioxidant effects on mice, including increased GSH-Px, GGT, and GSH levels in the liver and increased CAT and SOD levels in the kidney. HepG2 cells experiments showed that C-phycocyanin exhibited none of the prevention effects on cisplatin injury. Faecalibaculum showed the greatest reduction among genera after cisplatin treatment, which was related to the enrichment of Romboutsia and Lactobacillus genera. C-phycocyanin treatment reduced the populations of harmful bacteria of Enterococcus faecalis, which was positively correlated with inflammation induced by cisplatin. C-phycocyanin increased the contents of 23-nordeoxycholic acid and β-muricholic acid. Moreover, C-phycocyanin increased amino acid-related metabolites, Nα-acetyl-arginine and trimethyl-lysine contents, and decreased fatty acid esters of hydroxy fatty acids (FAHFAs) contents. In conclusion, C-phycocyanin inhibited inflammation via the 23-nordeoxycholic acid-Enterococcus faecalis-inflammation axis, and enhanced the antioxidant capacity of kidney via Lactobacillus-NRF2 pathway. C-phycocyanin alleviated cisplatin injury via the modulation of gut microbiota, especially Lactobacillus and Enterococcus, as well as regulation of metabolites, especially bile acid and FAHFAs, which highlight the effect of C-phycocyanin and provide a new strategy to prevent cisplatin injury.